Aripiprazole Facilitates Extinction of Conditioned Fear in Adolescent Rats - Ganella, Despina E.; Lee-Kardashyan, Liubov; Luikinga, Sophia J.; Nguyen, Danny L. D.; Madsen, Heather B.; Zbukvic, Isabel C.; Coulthard, Russell; Lawrence, Andrew J.; Kim, Jee Hyun (Frontiers in Behavioral Neuroscience, 2017)
Anxiety disorders are the most common type of mental disorder during adolescence, which is at least partly due to the resistance to extinction exhibited at this age. The dopaminergic system is known to be dysregulated during adolescence; therefore, we aimed to facilitate extinction in adolescent rats using the dopamine receptor 2 partial agonist aripiprazole (Abilify™), and examine the behavioral and neural outcomes. Adolescent rats were conditioned to fear a tone. The next day, rats received extinction 30 minutes after a systemic injection of either 5mg/kg aripiprazole or vehicle, and then were tested the following day. For the immunohistochemistry experiment, naïve and ‘no extinction’ conditions were added and rats were perfused either on the extinction day or test day. To assess the activation of neurons receiving dopaminergic input, c-Fos and dopamine- and cAMP-regulated neuronal phosphoprotein (DARPP-32) labeled neurons were quantified in the amygdala and the medial prefrontal cortex (mPFC). Systemic treatment with aripiprazole at the time of extinction significantly reduced freezing at test the next day. This effect was not observed in rats that were fear conditioned but did not receive any extinction. Aripiprazole’s facilitation of extinction was accompanied by increased activation of neurons in the mPFC. Taken together, aripiprazole represents a novel pharmacological adjunct to exposure therapy worthy of further examination. The effect of aripiprazole is related to enhanced activation of mPFC neurons receiving dopaminergic innervation.